2020
DOI: 10.5539/jel.v9n4p1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coronavirus (Covid19) Outbreak on Education Systems: Evaluation of Distance Learning System in Turkey

Abstract: Due to Covid19, measures have been taken to minimize interaction, maintain social isolation, and ensure interpersonal social distance. As a result of these decisions taken by the authorities, educational activities in Turkey were suspended at first. After some time, lessons were given in the form of distance learning on digital platforms. This research was carried out to evaluate the efficiency, positive and negative aspects of the distance learning system, and its shortcomings from the viewpoints of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
2
14
1
Order By: Relevance
“…Hence, the findings of the study in this respect revealed that almost all of the respondents preferred to have face-to-face teaching, while fewer respondents preferred to have online teaching. The findings of the study are in line with the studies conducted by (Beltekin & Kuyulu, 2020;Surahman & Sulthoni, 2020) whose findings revealed that online taught course was not as effective as face-to-face teaching. In other words, their respondents preferred face-to-face teaching over online teaching.…”
Section: Discussionsupporting
confidence: 84%
“…Hence, the findings of the study in this respect revealed that almost all of the respondents preferred to have face-to-face teaching, while fewer respondents preferred to have online teaching. The findings of the study are in line with the studies conducted by (Beltekin & Kuyulu, 2020;Surahman & Sulthoni, 2020) whose findings revealed that online taught course was not as effective as face-to-face teaching. In other words, their respondents preferred face-to-face teaching over online teaching.…”
Section: Discussionsupporting
confidence: 84%
“…This new situation can tire students and lead them to become critical of classes [ 44 ]. According to Barnes [ 12 ], time management, teachers’ low expectations/inconsistency, and continual student needs interfered with academic achievement, and systemic technical problems hindered students’ academic motivation [ 45 ]. This study’s findings, regarding students’ disappointment about non-face-to-face classes, align with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Gilmore et al, (2020) found community engagement structures and the use of community engagement approaches supported contextually specific, acceptable and appropriate COVID-19 prevention and control measures. Beltekin & Kuyulu (2020) found that measures have been taken to minimize interaction, maintain social isolation, and ensure interpersonal social distance. As a result of these decisions taken by the authorities, educational activities in Turkey were suspended at first.…”
Section: Discussionmentioning
confidence: 99%